Caracterização funcional da ORF hipotética XAC3407 codificada por Xanthomonas citri subsp. citri - Santos, Bianca da Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Citrus canker is a disease that affects all the commercially important citrus varieties, caused by the Gram-negative bacterium Xanthomonas citri subsp. citri (Xac). Infection generates necrosis in plants, especially in the foliar area, which in severe cases may cause fruit drop, leading to a decrease in production and quality of the fruits. Symptomatic fruits may yet be used by the juice industry; However, they have no use for table market. Citrus canker has no cure, and eradication of infected plants continues to be the best measure to control the spread of the bacterium. Knowledge about the biology of the etiological agent is therefore a good way to devise strategies of disease spread and control. Our group has dedicated efforts to understand the cell division process of Xac. Since perturbation of cell division is an excellent strategy to inhibit bacterial growth and infection, we have developed compounds that target the main protein constituent of the divisional septa. Here, we intend to study a novel polypeptide encoded by a hypothetical ORF, XAC3407, which apparently is involved with cell division. This ORF was identified in protein-protein analyses in which we used as bait Xac ZapA, a well-known cell division/FtsZ-stabilizer factor. XAC3407 was expressed in Xac by a fusion with Green Fluorescent Protein (GFP) in its N- terminal and visualized in fluorescent microscopy. The sub-cellular localization pattern observed for this ORF was a perpendicular bar to the longitudinal axis of the cell, arranged in the center of the rod, the middle of the cell, co-localizing with the division septum. In bioinformatic analysis, we observed that this ORF is annotated as ZapB in KEGG database, besides, it also showed high similarity and identity with proteins from related organisms annotated as ZapB. However, in alignment with ZapB from Escherichia coli it presented low identity/similarity, but they display the same sub-cellular localization pattern...

O cancro cítrico é uma doença que afeta os citros de importância econômica e é causado pela bactéria Gram-negativa Xanthomonas citri subsp. citri (Xac). A infecção por Xac produz necroses nas plantas, principalmente nas áreas foliares, também podendo causar queda prematura dos frutos, ocasionando uma diminuição na sua produção e qualidade, além da debilitação da árvore. Frutos sintomáticos podem até ser utilizados para extração de suco, porém, não se adequam ao mercado de mesa. Por ser uma doença incurável, o cancro deve ser evitado mediante erradicação de plantas doentes ou técnicas de manejo que evitam o espalhamento da bactéria pelos pomares. Neste sentido, o conhecimento da biologia do patógeno representa uma das armas para se controlar a doença. Nosso grupo iniciou, há aproximadamente 10 anos, pesquisas sobre o processo de divisão celular de Xac, com o intuito de perturbá-lo e inibir o crescimento da bactéria, desenvolvendo também compostos que afetem a principal proteína formadora do septo divisional. Neste trabalho, caracterizamos a ORF hipotética de Xac que aparentemente está envolvida na formação do septo. Esta ORF (XAC3407) foi identificada em experimentos de interação proteína-proteína realizados por nosso grupo, onde utilizamos como isca outra proteína, ZapA, que faz parte do septo e tem papel na sua formação e estabilização. XAC3407 foi expressa em Xac em fusão com Green Fluorescent Protein (GFP) em sua porção N-terminal para visualização em microscopia de fluorescência. O padrão de localização observado foi uma barra perpendicular ao eixo longitudinal da célula, disposto no centro do bastonete, co-localizando com o septo de divisão. Nas análises de bioinformática vimos que essa ORF se encontra anotada como ZapB no banco de dados KEGG, além de possuir alta similaridade e identidade com proteínas de organismos próximos também anotadas como ZapB. Apesar de...
Keywords: Xanthomonas campestris; Cancro citrico; Bactérias; Citologia; Proteínas